Gender differences in brand attitude towards real unhealthy and fictitious healthy brands: The role of slogan familiarity - Mohd Amin, Noraziah; Tugiman, Nursafwah; Sharipudin, Mohamad-Noor Salehhuddin (Taylor's University, 2023)
The effectiveness of brand slogans (also referred to as slogans in this study) in communicating product information has been widely discussed, but there is limited research on whether consumers familiarity with slogans differs for healthy and unhealthy products, and whether gender plays a role in this context. This study investigates consumer familiarity with real unhealthy and fictitious healthy slogans and examines how consumers evaluate these slogans, which ultimately influences their brand attitude. A mixed-method approach was employed to address the research questions and hypotheses. First, a content analysis was conducted using relevant literature on slogan familiarity and brand attitude from 2007 to 2022. Subsequently, advertisement stimuli were developed based on the content analysis findings. Next, a questionnaire survey was conducted involving 122 local university students in Malaysia. The results indicate that respondents who were familiar with real slogans tended to have a positive attitude towards real brands, while participants more familiar with fictitious healthy brands exhibited a positive attitude towards fictitious healthy brands. Interestingly, gender was found to interact with slogan familiarity, specifically for fictitious healthy brands, and this effect was predominantly true for female participants only. Female consumers were found to be more affected by the slogan or messaging strategy for healthy products compared to male consumers, even for unfamiliar brands. Based on the research findings, marketers may consider tailoring their branding strategies to align with their target consumers brand exposure, slogan familiarity, and demographic characteristics, such as gender.